Breaking Down Institutional Barriers to Advanced Practice Registered Nurse Practice. Issue 2 (April 2022) - Kleinpell, Ruth; Myers, Carole R.; Likes, Wendy; Schorn, Mavis N.
Abstract : Advanced practice registered nurses (APRNs) significantly contribute to health promotion, disease prevention, and disease management. Yet, barriers to APRN practice exist, including regulatory, state, and institutional barriers, that hinder their ability to practice to the full extent of their education, licensure, and certification. Nurse leaders can play an important role in helping reduce unnecessary institutional barriers to APRN practice.